2016
DOI: 10.1128/jcm.03321-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Luminex xTAG Gastrointestinal Pathogen Panel Assay for Detection of Multiple Diarrheal Pathogens in Fecal Samples in Vietnam

Abstract: Diarrheal disease is a complex syndrome that remains a leading cause of global childhood morbidity and mortality. The diagnosis of enteric pathogens in a timely and precise manner is important for making treatment decisions and informing public health policy, but accurate diagnosis is a major challenge in industrializing countries. Multiplex molecular diagnostic techniques may represent a significant improvement over classical approaches. We evaluated the Luminex xTAG gastrointestinal pathogen panel (GPP) assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…Ten studies [20][21][22][23][24][25][26][27]29,30 reported results of association between the comparator and the GPP test in sufficient detail by pathogen to allow the construction of 2 × 2 tables by pathogen. These studies are further characterised in Table 7 and contributed data to the meta-analysis in Pathogen-level positive and negative agreement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies [20][21][22][23][24][25][26][27]29,30 reported results of association between the comparator and the GPP test in sufficient detail by pathogen to allow the construction of 2 × 2 tables by pathogen. These studies are further characterised in Table 7 and contributed data to the meta-analysis in Pathogen-level positive and negative agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies tested all samples with comparator methods, but these were not equivalent to conventional methods of the PHE algorithm. 20,25 In three studies, 22,24,30 samples had received all conventional methods, but the studies only looked at a limited number of pathogens, and Gu et al 26 constructed a comparator for which conventional methods were undertaken according to the physician's judgement, but additional testing for astrovirus, norovirus and sapovirus was undertaken for all samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations